Improving Digital Marketing Literacy Capability of Breeders of Rumah Maggot, Barepan Bangkit Yogyakarta in Facing the VUCA Era - Pardimin Pardimin; Imam Ghozali; Wahyu Setya Ratri; Agustinus Eko Susetyo; Siti Rochmiyati; Syamsul Hadi; Didi Supriadi; Dinar Westri Andini; Rahadi Rahadi; Indah Kurniasih (Faculty of Economics Universitas Sarjanawiyata Tamansiswa, 2023)
Purpose This community service aims to to increase digital marketing literacy skills for breeders of Rumah Maggot Barepan Bangkit Yogyakarta in facing the VUCA era. Methods-Methode community service acitivities. Result and discussions-the result report and the information about the acitivities. Conclusion- This mentoring process activity resulted in program success targets including sharing and discussion of business management management to overcome business management problems reaching 90%, and discussions and practices of marketing network effectiveness, optimization of promotional/advertising media to overcome marketing media problems and optimization reaching 90%. Our advice is concerns the this is important to continue and develop when the mentoring program is over and can be passed on to other groups of breeders because again, that the success of a business depends on leaders who can manage and optimize existing resources such as the concept of Ki Hajar Dewantara's leadership as a leader must be able to ing ngarso sung tulodo, madyo mangun karso, and tut wuri handayani meaning that being a leader must be able to set a good example, in the midst of his busy schedule he must also be able to arouse or inspire enthusiasm, and a person must provide moral encouragement and enthusiasm for work from behind. Keywords: digital marketing, literacy capability of breeders, facing the VUCA era